The Imprisonment of Women in Scotland: Restructure, Reform or Abolish? - Malloch, Margaret (2017)
The use of imprisonment and non-custodial alternatives for women in Scotland has remained a focus of attention in the 10 years since the publication of the Corston report. However, events in Scotland have been influenced to a greater extent by the Commission on Women Offenders (2012) which called, among other things, for the closure of HMP and YOI Cornton Vale, Scotland's national prison for women. The Commission's recommendations focused considerable attention on the structural organisation of the prison system in relation to women, a commitment to new forms of custody and more effective use of 'punishment in the community'. However, the 'fragmented landscape' of community provisions remains a focus of concern for penal reformers and as this paper will argue, the potential for radical change in Scotland – as in England and Wales – requires a more critical analysis of 'justice' for women